Suhu Tubuh Pada Pasien Demam dengan Menggunakan Metode Tepid Sponge - Ketut Labir; I Nyoman Ribek (Jurnal Gema Keperawatan, 2017)
The aim of this research is to know the description of body temperature in patients with fever by using tepid sponge method. This research is descriptive type with crosssectional approach. The sampling technic is nonprobability sampling kind, that is concecutive sampling. The sample amount is 60 respondents andthis research was going on April-Mei 2017. The data was taken with participant observation and was analyze with computer system in frequency-distribution table. The results showed a decrease in body temperature both immediately after the action and 30 minutes after the action, with each are 0.70C and 1.20C.